The linkage between international trade and economic growth in Kazakhstan - Akhter, Sabina; Mir, M Afzal; Megits, Nikolay (Journal of Eastern European and Central Asian Research (JEECAR), 2022)
Increased international trade flows and reduced trade restrictions have sparked ongoing debate and discussion about the influence of international trade on economic progress. Based on the empirical evaluation, the paper investigates the impact of trade openness on Kazakhstan's economic growth in a multivariate framework. It includes investment, international trade, labour force, human capital, and natural resource as explanatory constructs when gross domestic product per capita is the regressand variable. This research aims to assess the long-term relationship between trade and income development in Kazakhstan from 1992 to 2020. The Phillips and Perron (1988) and augmented Dickey and Fuller (1981) tests are used to check data stationarity. The bound test shows that the concerned variables have a long-term relationship. The results conclude that trade negatively impacts growth in the short and long run. While capital formation, labour quantity, quality, and natural resources positively affect the development of Kazakhstan's economy. This negative impact of trade on growth could be attributed to the country's shortage of good institutions and inefficient management, economic structure, and development policies. Also, it could be due to the substantial negative impact of imports countering the positive effect of exports.